An Approach to Estimate the Outstanding Loss Reserve of the Non-Life Insurer Under Solvency- II Regime - Mohd Ilyas, Ashiq; Rajasekaran, S (International Journal of Engineering and Technology, 2018)
This paper studies the reserve risk estimation requirement under the Solvency-II regime that came into effect in the European insurance sector in January 2016. In particular, it shows how the outstanding loss of a non-life insurer can be estimated under this regime. This regime totally replaces the traditional approaches of providing standard deviations of the liabilities over their full run-off. The requirement under this regime is that each risk shall be calibrated using a value-at-risk measure with 99.5 percentile confidence level over a single period. In connection with this, a bootstrap framework is used to estimate the uncertainty of loss reserve over the single period time horizon. Two process distributions are used namely Over-dispersed Poisson and Gamma in two separate bootstraps to estimate the uncertainty of loss reserve. Further, a comparison is established in the estimated results and it is found that Over-dispersed Poisson process distribution produces lower prediction errors than the gamma process distribution.Â Â